Delivery of DNA-Based Therapeutics for Treatment of Chronic Diseases - Carleigh Sussman; Rachel A. Liberatore; Marek M. Drozdz (MDPI AG, 2024)
Gene therapy and its role in the medical field have evolved drastically in recent decades. Studies aim to define DNA-based medicine as well as encourage innovation and the further development of novel approaches. Gene therapy has been established as an alternative approach to treat a variety of diseases. Its range of mechanistic applicability is wide; gene therapy has the capacity to address the symptoms of disease, the body's ability to fight disease, and in some cases has the ability to cure disease, making it a more attractive intervention than some traditional approaches to treatment (i.e., medicine and surgery). Such versatility also suggests gene therapy has the potential to address a greater number of indications than conventional treatments. Many DNA-based therapies have shown promise in clinical trials, and several have been approved for use in humans. Whereas current treatment regimens for chronic disease often require frequent dosing, DNA-based therapies can produce robust and durable expression of therapeutic genes with fewer treatments. This benefit encourages the application of DNA-based gene therapy to manage chronic diseases, an area where improving efficiency of current treatments is urgent. Here, we provide an overview of two DNA-based gene therapies as well as their delivery methods: adeno associated virus (AAV)-based gene therapy and plasmid DNA (pDNA)-based gene therapy. We will focus on how these therapies have already been utilized to improve treatment of chronic disease, as well as how current literature supports the expansion of these therapies to treat additional chronic indications in the future.